THE DESIGN OF EVOLUTIONARY ALGORITHMS: A COMPUTER SCIENCE PERSPECTIVE ON THE COMPATIBILITY OF EVOLUTION AND DESIGN - Jeavons, Peter (Zygon, 2022)
The effectiveness of evolutionary algorithms is one of the issues discussed in The Compatibility of Evolution and Design, where it is argued that such algorithms are only effective when stringent preconditions are met. This article considers this issue from the perspective of computer science. It explores the properties of problems that can be effectively solved by evolutionary algorithms, and the extent to which such algorithms need to be carefully adjusted. Although there are important differences between the study of evolutionary algorithms in computer science and the study of biological evolution, it is argued that the experience of computer science can help to strengthen the claim that evolutionary mechanisms generally require a considerable degree of fine‐tuning.